2010
DOI: 10.1055/s-0030-1258767
|View full text |Cite
|
Sign up to set email alerts
|

Nitroethane in Polyphosphoric Acid: A New Reagent for Acetamidation and Amination of Aromatic Compounds

Abstract: A new method of acetamidation of aromatic compounds based on their reaction with nitroethane in polyphosphoric acid has been developed. Upon the hydrolysis of acetamides during the reaction mixture workup, the corresponding amines can be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Although nitroalkanes ( 4 ) normally behave as pronucleophilic species; in a polyphosphoric acid medium they are stabilized in a form of phosphorylated nitronates ( 5 ) with profound electrophilic properties. These phosphorylated nitronates tend to react with various carbon-based nucleophiles, for instance electron-rich arenes, allowing for Friedel–Crafts-type C–H functionalization reactions, often with subsequent accompanying rearrangements [ 21 , 22 , 23 , 24 ]. Furthermore, it was found that nitrogen-based nucleophiles ( 6 ), such as aliphatic amines [ 25 , 26 , 27 ], anilines [ 28 , 29 , 30 , 31 ], or hydrazines [ 32 , 33 ], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although nitroalkanes ( 4 ) normally behave as pronucleophilic species; in a polyphosphoric acid medium they are stabilized in a form of phosphorylated nitronates ( 5 ) with profound electrophilic properties. These phosphorylated nitronates tend to react with various carbon-based nucleophiles, for instance electron-rich arenes, allowing for Friedel–Crafts-type C–H functionalization reactions, often with subsequent accompanying rearrangements [ 21 , 22 , 23 , 24 ]. Furthermore, it was found that nitrogen-based nucleophiles ( 6 ), such as aliphatic amines [ 25 , 26 , 27 ], anilines [ 28 , 29 , 30 , 31 ], or hydrazines [ 32 , 33 ], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that upon heating in polyphosphoric acid, the nitroalkanes 1 convert into the phosphorylated nitronates 2 , which exhibit strong electrophilic properties. This allowed for the employment of these species in reactions wherein electron-rich arenes serve as carbon-based nucleophilies [ 38 40 ]. It was also discovered that the nucleophilic amines 3 can be successfully employed in this type of transformations as well, providing the amidinium intermediates 4 , which are susceptible to a variety of subsequent cyclizations.…”
Section: Resultsmentioning
confidence: 99%
“…This unusual species can be used to design a number of one-pot multi-step transformations involving various carbon-based nucleophiles. [17][18][19] The utilization of nucleophilic amines was also demonstrated. [20][21][22][23][24] Mechanistically, the latter process is related to the classical Nef reaction, [25][26][27] employing aniline [20][21][22][23] or hydrazine 24 species 8 instead of water.…”
Section: Resultsmentioning
confidence: 99%